A MODEL OF IMPROVING STUDENTS' KNOWLEDGE OF PRESERVING THE NATIONAL MUSICAL HERITAGE BASED ON AN AXIOLOGICAL APPROACH - Mansurova Nigoraxon Rustamjonovna (Scholars Digest Publishing, 2025)
This article has developed a model for improving students' knowledge of preserving national musical heritage, as well as empirically tested indicators, proposals and recommendations of students' knowledge of national musical heritage. Theoretical, empirical, and mathematical methods were used in the research work. As a result of this research, based on the axiological approach, the levels and criteria of integration of students' knowledge of preservation of national musical heritage, as well as empirical data on the research work, are presented. At the end of the article, conclusions and developed scientific-methodological recommendations are given.
Keywords: Musical inheritance, axiological approach, musical pedagogy, classical music, instrumental performance, vocal performance.